2018
DOI: 10.2147/cpaa.s161024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic equivalence study of nonsteroidal anti-inflammatory drug etoricoxib

Abstract: PurposeThe current study aimed to evaluate whether a generic product of etoricoxib 120 mg film-coated tablet (the test drug) was bioequivalent to the reference product (Arcoxia® film-coated tablet 120 mg).MethodsThis was a randomized, open-label, two-sequence, crossover study under fasting condition, with a 14-day washout period, involving 26 healthy adult male and female subjects. Blood samples were taken and analyzed for plasma concentrations of etoricoxib (Chemical Abstracts Service [CAS] 202409-33-4) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…The global regulatory requirement for the equivalent BA, or the BE, of medications with different formulations has become crucial in medicine and pharmaceutical development. 26 FDA guidance of BA and BE studies for orally administered drug products suggests that studies to measure BA and/or establish BE of a product are important elements in support of investigational new drugs (INDs), new drug applications (NDAs), abbreviated new drug applications (ANDAs), and their supplements. BA studies focus on determining the process by which a drug is released from the oral dosage form and moves to the site of action.…”
Section: Discussionmentioning
confidence: 99%
“…The global regulatory requirement for the equivalent BA, or the BE, of medications with different formulations has become crucial in medicine and pharmaceutical development. 26 FDA guidance of BA and BE studies for orally administered drug products suggests that studies to measure BA and/or establish BE of a product are important elements in support of investigational new drugs (INDs), new drug applications (NDAs), abbreviated new drug applications (ANDAs), and their supplements. BA studies focus on determining the process by which a drug is released from the oral dosage form and moves to the site of action.…”
Section: Discussionmentioning
confidence: 99%
“…The solubility analysis for ETX revealed that pure powder has low solubility in phosphate buffer (pH 7.4), while ETX NS showed comparatively higher solubility, as seen in Table 2. The prepared structure of NS increased surface area and improved hydrophilicity by reducing the particle size of ETX to the nanoscale using EC and PVA as well as hydrogen bonding between drug and nanosponges structure [12,13]. The solubility of prepared NS was significantly affected by increasing quantities of EC with constant amounts of ETX, as seen in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, supplementation of some vitamins together with anti-TB drugs has been shown to improve chemotherapy outcomes (Vilcheze et al, 2018). Clinical trials have shown that Vc supplementation improves the healing process in tuberculosis patients (Tjandrawinata et al, 2018), although no clinical improvement (sputum conversion) of patients was observed when using vitamin D (V D ). Therefore, the mechanism by which some vitamins can ammeliorate TB requires further investigation.…”
Section: Discussionmentioning
confidence: 99%